Characterizing CD38 expression in terminally differentiated B cells using variable lymphocyte receptor B tetramers - Nair, Arundhati G.; Leon-Ponte, Matilde; Kim, Vy HD; Sussman, Gordon; Ehrhardt, Götz R.A.; Grunebaum, Eyal (Frontiers in Immunology, 2024)
Introduction: CD38 is an ectoenzyme receptor found on hematopoietic cells and its expression is used in the flow cytometric analysis of sub-populations of circulating B cells among peripheral blood mononuclear cells (PBMC) to aid in diagnosing patients with different antibody production defects (AbD). Monoclonal antibodies derived from the sea lamprey Variable Lymphocyte Receptor B (VLRB) are emerging as an alternative to conventional mammalian antibodies. We hypothesized that VLRB MM3 (V-CD38) which specifically recognizes CD38 in a manner correlating with its enzymatic activity could identify terminally differentiated B cells in human PBMC. Here we investigate the ability of V-CD38 as a tool to diagnose patients with diverse immune abnormalities including AbD.Methods: The expression of CD38 on CD3 -CD19 + CD27 + plasmablasts and CD3 - CD19 + IgM hi CD27 -transitional B cells in PBMC was analyzed by flow cytometry using V-CD38 and compared with a commercial conventional antibody to CD38 (C-CD38).Results: A highly significant correlation (p<0.001, r=0.99) between the percentages of plasmablasts recognized by V-CD38 and C-CD38 was observed among 36 healthy controls (HC), 7 patients with AbD and 24 allergic individuals (AI). The use of V-CD38 enabled improved gating of the CD38 expressing cells (CD38+), aiding in the observation that patients with AbD had significantly lower (p=0.002) CD38+ plasmablasts (0.13%±0.13%) than HC (0.52%±0.57%). Only 61.3% of the transitional B cells detected by C-CD38 were also recognized by V-CD38 (r=0.95, p<0.001) among the 67 participants. AI had significantly reduced V-CD38 and C-CD38 transitional cells compared to HC (p=0.026 and p=0.012, respectively).Conclusions: V-CD38 is a novel reagent that can assess B cells in human PBMC.